Measuring the electric fields in space - Kun Li; Jun Cui; Yong Wei (地球与行星物理论评, 2021)
Measuring electric fields in the space environments of the Earth and other planets helps us to understand the electric field structures and plasma waves in the space. An addition usage of data from electric field measurements is to derive the cold ions in the magnetosphere which are invisible to ordinary energy spectrometers. The cold ions of ionospheric origin dominate the ion population in the magnetosphere. They are accelerated by the ambipolar electric field in the ionosphere to escape velocities. The loss of cold ions plays an important role in evolution of the atmosphere and habitability. In this review, we summarize two types of electric field instruments being widely used in space exploration, and the method to derive parameters of cold ions in the magnetosphere from the measurements made by the two types of electric field instruments. Based on existing technologies, we propose a new instrument to measure the ambipolar electric field in the polar region with a magnitude of about 10−6 Vm−1. This new instrument may be onboard a future satellite operating in the polar region, and give us clues on evolution of atmosphere and habitability.